Bicuspid Aortic Valve: a Review with Recommendations for Genetic Counseling. Issue 6 (22nd August 2016) - Freeze, Samantha L.; Landis, Benjamin J.; Ware, Stephanie M.; Helm, Benjamin M.
Abstract: Bicuspid aortic valve (BAV) is the most common congenital heart defect and falls in the spectrum of left‐sided heart defects, also known as left ventricular outflow tract obstructive (LVOTO) defects. BAV is often identified in otherwise healthy, asymptomatic individuals, but it is associated with serious long term health risks including progressive aortic valve disease (stenosis or regurgitation) and thoracic aortic aneurysm and dissection. BAV and other LVOTO defects have high heritability. Although recommendations for cardiac screening of BAV in at‐risk relatives exist, there are no standard guidelines for providing genetic counseling to patients and families with BAV. This review describes current knowledge of BAV and associated aortopathy and provides guidance to genetic counselors involved in the care of patients and families with these malformations. The heritability of BAV and recommendations for screening are highlighted. While this review focuses specifically on BAV, the principles are applicable to counseling needs for other LVOTO defects.